2023
DOI: 10.3390/s23073426
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Timed Up and Go Test (iTUG)—More Than Assessing Time to Predict Falls: A Systematic Review

Abstract: The Timed Up and Go (TUG) test is a widely used tool for assessing the risk of falls in older adults. However, to increase the test’s predictive value, the instrumented Timed Up and Go (iTUG) test has been developed, incorporating different technological approaches. This systematic review aims to explore the evidence of the technological proposal for the segmentation and analysis of iTUG in elderlies with or without pathologies. A search was conducted in five major databases, following PRISMA guidelines. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Regarding functionality, our findings are in agreement with the research of Carvalho et al (2015) which reported significant differences for the TUG test, with worse results in elderly women with fall history. This is a widely used tool to assess the functional conditions of elderly people as risk of falls ( Ortega-Bastidas et al, 2023 ). However, results for the SPPB test battery were not significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding functionality, our findings are in agreement with the research of Carvalho et al (2015) which reported significant differences for the TUG test, with worse results in elderly women with fall history. This is a widely used tool to assess the functional conditions of elderly people as risk of falls ( Ortega-Bastidas et al, 2023 ). However, results for the SPPB test battery were not significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…To identify potential articles, the electronic databases PubMed/MEDLINE, CINAHL, Web of Science, Cochrane Library and IEEE Xplore were searched on July 6, 2022. Reference lists of three relevant reviews on the iTUG [ 13 15 ] and of included articles were searched.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reviews on the iTUG focused on the different technologies utilized for TUG instrumentation [ 13 ], feasibility of the iTUG in mobile devices [ 14 ], and technological proposals in studies on fall risk analysis [ 15 ]. Two major approaches have matured to objectively and accurately capture a subject’s gait pattern: wearable inertial measurement units (IMUs) and non-portable systems such as camera-based optical motion capturing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge [3], an iTUG evaluation on people with phlebopathy is still missing. Therefore, the aim of this study is to test the specificity of iTUG subphases in detecting differences between phlebopathic patients and a healthy control group using SISTINE 3.0.…”
Section: Introduction and Methodsmentioning
confidence: 99%